VistaCreate y Heyzine Flipbook como herramientas de enseñanza aprendizaje de Química Orgánica con los estudiantes de sexto semestre de la Carrera de Ciencias Experimentales Química y Biología. - Vallejo López, Gabriela Stephania (2024)
Learning and Knowledge Technologies (TAC) and education are intertwined to facilitate the teaching-learning process of organic chemistry. However, only some authentic and interactive digital spaces allow us to face challenges such as lack of interest or motivation and difficulties understanding and acquiring information from unreliable sources. Therefore, the purpose of this research was to propose VistaCreate and Heyzine Flipbook as teaching-learning tools of Organic Chemistry with sixth-semester students of the Pedagogy of Experimental Sciences Chemistry and Biology. The methodology used in this study was developed under a quantitative approach, with a non-experimental design, exploratory and descriptive in level and scope, basic objective, field and bibliographic, cross-sectional. To collect data, the survey technique was used with its instrument, the questionnaire, which was applied to a population of 18 individuals after the socialization of the proposal. After the analysis and discussion of the results, it is concluded that the digital tools VistaCreate and Heyzine Flipbook are initiatives to strengthen the educational process since they facilitate the development of interactive and attractive material.